The Investigation of Customer’s Mobile-Banking Adoption in Azerbaijan - Musayeva, Nazrin (ADA University, 2022)
The purpose of this study is to determine the factors that increase customers’ willingness to adopt mobile-banking services in Azerbaijan. In addition, the primary and quantitative data was collected through online questionnaires using the convenience sampling method. Similarly, the utilized theoretical framework included TAM and its extensions. To elaborate, the research investigated the relationship between five independent variables: perceived usefulness, perceived ease of use, perceived risk, social media, social influence and the dependent variable which was the intention to adopt. Moreover, the following variables such as age, gender, marital status, job, income, and education were integrated into the model to control the variance driven from the differences in consumer characteristics. In total, 206 responses were collected and analyzed using ordered logistic regression. The findings demonstrated a significant relationship between all the independent variables and intention to adopt. While perceived ease of use, perceived usefulness, social media, and social influence were positively correlated with customers’ adoption intention, the risks associated with m-banking usage discouraged respondents from utilizing it more frequently. Notably, the results varied depending on the individuals’ gender, education, age, job, and marital status. The study gives implications for the future researches by providing them with a valid framework in the interpretation of consumers’ intention to adopt mobile banking. Similarly, the findings provide bank managers’ with valuable insights into consumer behavior by determining the factors stimulating their m-banking adoption. Consequently, it enables them to formulate marketing strategies to increase users’ mobile banking adoption rate in Azerbaijan.
Keywords: Mobile applications.; Mobile-banking.; Mobile-banking -- Azerbaijan.; Business